Fear of Crime Out West: determinants of Fear of Property and Violent Crime in Five States - Lee, Heeuk D. (International journal of offender therapy and comparative criminology, 2020)
Fear of crime research has been around for decades, and many studies of its extent, nature, and consequences have been published. In this study, we build upon existing research to examine the effects of vulnerability, disorder/incivilities, social cohesion, prior victimization, and perceptions of police upon fear of property crime and fear of violent crime. Using data from a random mail survey of residents from five different states, the current study offers a view of the determinants of fear of crime within an often overlooked population—residents of the Western United States. Results support leading theories of fear of crime, finding that women, perceptions of disorder/incivilities, perceptions of social cohesion, prior victimization, and assessments of police quality of service each influence fear of crime. Findings also suggest that the determinants of fear of crime vary somewhat according to crime type.